An update on the underlying risk factors of eating disorders onset during adolescence: a systematic review - Varela, Carmen; Hoyo, Ángela; Tapia-Sanz, María Eugenia; Jiménez-González, Ana Isabel; Moral, Benito Javier; Rodríguez-Fernández, Paula; Vargas-Hernández, Yadirnaci; Ruiz-Sánchez, Luis Jorge (Frontiers in Psychology, 2023)
Eating disorders (EDs) are serious psychological problems that affect not only the individual, but also their entire environment. The prevalence rates of EDs are higher among the adolescent population. A better understanding of ED risk factors is essential to design effective prevention and intervention programs that focus beyond the areas of weight and appearance. The main objective of this systematic review was to identify the risk factors of EDs and provide a comprehensive approach, analyzing the interplay between individuals, their inner circle, and the society characteristics. The Web of Science, Scopus, CENTRAL and PsycInfo databases were searched. The initial search produced 8178 references. After removing duplicates and performing the selection process by three independent reviewers, 42 articles were included in the systematic review according to the pre-specified inclusion criteria. The results suggest the relevance of society and the inner circle on the development of EDs. The internalization of the thin ideal, promoted by the current society, and living in an unsupportive, unaffectionate, non-cohesive environment were associated with the onset of EDs symptomatology. Other associated variables with this ED indicator were poor-quality relationships and feeling judged about appearance. These aspects seem to be essential for the development of individual characteristics like self-esteem or adaptative coping during adolescence. This systematic review has shown the complex etiology of EDs and the relevance of the interplay between the different areas involved. Furthermore, this information could be relevant to improve the design of innovative and more effective prevention and intervention programs.